Evaluation of the efficiency of some organic solvent extract of Leaves and Flowers of Chrysanthemum cinerariaefolium against the immature stages of Culex quinquefasciatus Say (Diptera:Culicidae) - O.Kreem, Ruqia; R. Annon, Mohammed (Al-Qadisiyah Journal of Pure Science, 2018)
The current research included the biological impact of some organic solvent extracts of Leaves and flowers of C. cinerariaefolium on the unaccumulated mortality of immature stages of mosquito Cx. quinquefasciatus . the results showed that the hexane extracts each of the Leaves and flowers had a higher impact on the mortality of an immature stages followed by ethyl acetate and ethyl alcohol extract respectively. eggs mortality precentages were recorded (36.57 -46.65 )% at 40 mg/ml of Leaves and flowers extracts respectively . First Larval instar showed a high sensitive than other proceeding instars . The high mortality rate recorded in hexane flowers extract of 40mg /ml (78.72 )% .in addition the hexane extracts of Leaves and flowers of C. cinerariaefolium showed a superior activity on pupal mortality rate than other ethyl acetate and ethel alcohol,and the mortality revceatay was reached ( 70.10 )%. The results also showed a direct correlation between the increase in concentration and mortality rates in all extracts and on different life stages .